Veno-venous surgical bypass for central vein occlusion in a child: The first in the literature - Karthigesu Aimanan; Ong, Mang Ning; Koay, Kean Leong; Siew, Caroline Yin Eng; Firdaus Hayati; Hafizan Tajri (Elsevier Ltd., 2023)
Introduction During the past two decades, the incidence of chronic kidney disease (CKD) in children worldwide has steadily increased and, even in children, native arteriovenous fistula (AVF) remains the access of choice. Nevertheless, maintaining a well functioning fistula is limited by central venous occlusion due to the widespread use of central venous access devices before AVF creation. Report A 10 year old girl with end stage renal failure dialysing through a left brachiocephalic fistula presented with left upper limb and facial swelling. She had previously exhausted the option of ambulatory peritoneal dialysis for recurrent peritonitis. A central venogram showed occlusion at the left subclavian vein, which was not amenable for angioplasty through either an upper limb or femoral approach. Given the precious fistula with concomitant worsening venous hypertension, an ipsilateral axillary vein to external iliac vein bypass was performed. Subsequently, her venous hypertension was significantly resolved. This report is the first in English literature on this surgical bypass in a child with central venous occlusion. Discussion Central venous stenosis or occlusion rates are rising due to extensive central venous catheter use in the paediatric population with end stage renal failure. In this report, an ipsilateral axillary vein to external iliac vein bypass was used successfully as a safe temporary option to maintain AVF. Ensuring a high flow fistula pre-operatively and continued antiplatelet post-operatively will allow longer patency of the graft.